Prevalence of Postnatal Depression and Its Risk Factors among Postnatal Women in Rural Area of Srikakulam District - Dhanalatha Tharigonda Reddy; Irfan Ali Syed; Dhananjaya Sharma; Satyajit Pattnaik; Jarina Begum; Samina Ausvi (Medsci Publications, 2020)
Introduction: During postpartum period women are at high risk for developing episodes of depression. Postnatal depression (PND) is a major public health issue because of its adverse effects on the infant and entire family. Objective: To find the prevalence of PND among postnatal(PN) women in Singupuram rural health training centre(RHTC) area, Srikakulam district, Andhra Pradesh and to find association between socio-demographic, obstetric and pregnancy outcomes and PND. Method: Sampling Method- Non-probability convenient sampling. This cross-sectional study was carried out among PN women (4th-10th week) in Singupuram RHTC area, Srikakulam district during May to August 2019. Details were collected using a pre-tested semi-structured questionnaire pertaining to socio-demographic profile, obstetric and pregnancy outcomes along with an Edinburg Postnatal Depression Scale (EPDS) translated into local language (telugu) cut-off score of ≥13 was used as high risk of PND. Result: The study included 229 PN women. Prevalence of PND was 28.3%. PND showed significant association (p<0.05) with type of family, working status of PN women, husbands occupation, socio-economic status, mode of delivery, gender of the newborn, and complications in pregnancy. Conclusion: PND among rural PN women is 28.3%. Early stage of PND screening and diagnosis should be included as  integral part of PN care.